Missing the Mark: The Complexity of African American Dementia Family Caregiving - Brewster, Glenna S (J Fam Nurs, 2020)
Alzheimer’s disease and related dementias (ADRD) have a significant impact on families. Family nurses are in an ideal position to address the needs of families affected by ADRD. However, to be most effective, family nurses and researchers need culturally appropriate theories to guide practice and research. On November 17, 2018, five nurse researchers presented findings of their research with African American families at the Gerontological Society of America’s annual meeting. The results reported and the lively discussion that ensued suggested that the current paradigms framing research and practice with African American families affected by ADRD may not be adequate. There is a need to consider culturally congruent, family-centered theories to guide research and practice.